2021
DOI: 10.1021/jacsau.1c00262
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Antibacterial Strategy Based on Reactive Oxygen Species Generated from Dioxygen Reduction Using an Organoruthenium Complex

Abstract: Pathogenic microorganisms pose a serious threat to global public health due to their persistent adaptation and growing resistance to antibiotics. Alternative therapeutic strategies are required to address this growing threat. Bactericidal antibiotics that are routinely prescribed to treat infections rely on hydroxyl radical formation for their therapeutic efficacies. We developed a redox approach to target bacteria using organotransition metal complexes to mediate the reduction of cellular O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 53 publications
(102 reference statements)
1
38
0
2
Order By: Relevance
“…10). 44 The initial strategy proposed by the authors lies on the exploitation of endogenous formate as a hydride Fig. 10 ROS generation by a ruthenium(II) complex inside bacterial cells: (A) hydride transfer mechanism in formate abundant Gram + strains and (B) SET mechanism in formate deficient strains.…”
Section: Cells Tests Performed Withmentioning
confidence: 99%
“…10). 44 The initial strategy proposed by the authors lies on the exploitation of endogenous formate as a hydride Fig. 10 ROS generation by a ruthenium(II) complex inside bacterial cells: (A) hydride transfer mechanism in formate abundant Gram + strains and (B) SET mechanism in formate deficient strains.…”
Section: Cells Tests Performed Withmentioning
confidence: 99%
“…In particular, a number of groups have demonstrated that half-sandwich arene ruthenium complexes are some of the most suitable for in vivo usage. [30][31][32][33][34][35][36][37][38][39][40][41][42] In a pioneering example of this field, the Meggers group showed that Cp*Ru(COD)Cl (Cp* = η 5 -pentamethylcyclopentadienyl, COD = η 4 -1,5-cyclooctadiene) 1 could be used to facilitate allylcarbamate (alloc) cleavage within living mammalian cells. [30] Subsequent studies have shown that besides alloc deprotection, [31] Cp*Ru(COD)Cl can also be used effectively for azide-thioalkyne cycloaddition.…”
Section: Metal Catalyst Complexesmentioning
confidence: 99%
“…[40] In one notable example, the Ang group set out to prepare and test a diverse library of 768 unique ruthenium arene Schiff-base complexes 6. [41,42] To facilitate this, they used a 3-component assembly method to screen and identify the highest yielding catalysts for sulfonyl azide reduction. As a result, they found 6 catalysts with high efficiencies to carry forward and showed that intracellular reactivity in bacteria was possible.…”
Section: Metal Catalyst Complexesmentioning
confidence: 99%
See 2 more Smart Citations